2003
DOI: 10.1002/rnc.732
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a solid propellant rocket instability by state feedback

Abstract: SUMMARYIn this paper a globally stabilizing feedback boundary control law for an arbitrarily fine discretization of a one-dimensional nonlinear PDE model of unstable burning in solid propellant rockets is presented. The PDE has a destabilizing boundary condition imposed on one part of the boundary. We discretize the original nonlinear PDE model in space using finite difference approximation and get a high order system of coupled nonlinear ODEs. Then, using backstepping design for parabolic PDEs, properly modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Because the transformation is invertible for an arbitrary grid choice, it can be concluded that the discretized version of the original system is asymptotically stable and we obtain a nonlinear feedback boundary control law for the density in the original set of coordinates. This technique, which avoids linearization of the model, has already been successfully applied to other physical applications in [8], [9], [10]. Numerical simulations of the resulting control laws show that the response time of density profiles is greatly improved with just one step of backstepping, or, in other words, with a single sensor measurement of the densities from within the plasma.…”
Section: Introductionmentioning
confidence: 90%
“…Because the transformation is invertible for an arbitrary grid choice, it can be concluded that the discretized version of the original system is asymptotically stable and we obtain a nonlinear feedback boundary control law for the density in the original set of coordinates. This technique, which avoids linearization of the model, has already been successfully applied to other physical applications in [8], [9], [10]. Numerical simulations of the resulting control laws show that the response time of density profiles is greatly improved with just one step of backstepping, or, in other words, with a single sensor measurement of the densities from within the plasma.…”
Section: Introductionmentioning
confidence: 90%
“…This equation is partly motivated by the model of unstable burning in solid propellant rockets [2]. But the most important reason to consider this plant is that it often appears as a part of the control design for more complicated systems (see Sections VIII and IX).…”
Section: B Other Spatially Causal Plantsmentioning
confidence: 99%
“…Using the above backstepping approach, the problem of finding the coordinate transformation (5) and the corresponding stabilizing boundary control (3) requires two steps.…”
Section: Open Problemmentioning
confidence: 99%
“…Superlinear nonlinearities can imply finite time blow-up for the uncontrolled case [6,7,9,10]. However, numerical results in a series of papers by Boskovic and Krstic [3,4,5] show promise for the applicability of the infinite dimensional backstepping to nonlinear problems, at least for finite-grid discretizations. In this note, we present the open problem of convergence of nonlinear backstepping schemes as the discretization grid becomes infinitely refined.…”
Section: Introductionmentioning
confidence: 97%